Validasi Metode Bioanalisis Vankomisin HCl dalam Spiked-plasma Manusia Menggunakan KCKT-UV untuk Aplikasi PKOD - Wibowo, Ari; Maulidina, Damas Inggil; Fitri, Wahyuni Shalatan; Ningrum, Vitarani (EKSAKTA: Journal of Sciences and Data Analysis, 2019)
As the first-line antibiotic for the treatment of infections caused by methicillin-resistant Staphylococcus aureus  (MRSA), vancomycin has  a narrow therapeutic index with high pharmacokinetic   variability. Therefore, it is deemed necessary to examine its concentration in the blood as a strategy to monitor the fulfillment of therapeutic levels  in patients receiving vancomycin. This study aimed to validate vancomycin bioanalysis  in  spiked-human  plasma  for  the  applications  of  therapeutic  drug  monitoring  (TDM).